2020
DOI: 10.1016/j.ajoc.2020.100958
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral macular hemorrhage in a patient with COVID-19

Abstract: Purpose We report a case of a patient with a known hereditary spherocytosis who developed a bilateral macular hemorrhage in concurrence with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-related respiratory syndrome. Observations Blood tests showed severe hemolytic anemia. Interestingly, the peripheral blood smear demonstrated a mixed pathogenesis of the hemolytic process (cold-agglutinin-mediated and non-immune-mediated due to spherocytosis). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…D'Aloisio R et al reported a case who developed bilateral retinal hemorrhages, involving the fovea in one patient [ 10 ]. These hemorrhages spontaneously resolved within a month.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D'Aloisio R et al reported a case who developed bilateral retinal hemorrhages, involving the fovea in one patient [ 10 ]. These hemorrhages spontaneously resolved within a month.…”
Section: Resultsmentioning
confidence: 99%
“…Authors also noted that fibrinogen, CRP, ferritin and LDH levels were all raised in the patients. D'Aloisio R et al reported a case who developed bilateral retinal hemorrhages, involving the fovea in one patient [10]. These hemorrhages spontaneously resolved within a month.…”
Section: Retinal Hemorrhages and Cotton Wool Spotsmentioning
confidence: 97%
“…A total of 14 case reports, two cross-sectional studies, and two prospective cohorts were included. Consequently, COVID-19 has been associated with several vitreoretinal abnormalities including central retinal vein occlusion (CRVO),[ 19 22 23 30 32 ] central retinal artery occlusion (CRAO),[ 17 ] serpiginous choroiditis,[ 29 ] chorioretinitis,[ 28 ] macular hemorrhage,[ 18 ] acute macular neuroretinopathy (AMN),[ 22 32 ] paracentral acute middle maculopathy (PAMM),[ 22 32 ] vitritis,[ 19 ] acute retinal necrosis (ARN),[ 21 ] and posterior segment anatomical changes[ 24 26 27 28 30 ] Summary of patients' ocular manifestations were listed in [ Table 2 ].…”
Section: Vitreoretinal Abnormalities In Covid-19 Patientsmentioning
confidence: 99%
“…Prothrombotic state and immune-mediated reactions triggered by COVID-19 infection can lead to retinal damage by endothelial dysfunction, which can cause cotton wool spots, edema and retinal hemorrhage clinically [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%